BIOLOGICAL TECHNOLOGY FOR PROCESSING THE ANTIMONY ORES AND CONCENTRATES - Solozhenkin P.M.; Lyalikova-Medvedeva N.N. (My University, 2001)
Processes of treatment of antimony ores have been considered. Microorganisms have been utilized for separation of antimony and mercury. Results of utilization of the microorganisms have been presented. Problems in technology for direct treatment of gold-antimony concentrates with the use of antimony pentachloride. Prospects for leaching the antimony using the alkaline solution of sulfate-reducing bacteria have been shown. Transformation of antimony sulfide and manufacturing of marketable product of antimony trioxide have been described. In this case, application of Thiobacillus ferrooxidans is noted.